Acousto‐Photolithography for Programmable Shape Deformation of Composite Hydrogel Sheets. Issue 47 (10th October 2022) - Li, Minghao; Mei, Jiyang; Friend, James; Bae, Jinhye
Abstract: Stimuli‐responsive hydrogels with programmable shapes produced by defined patterns of particles are of great interest for the fabrication of small‐scale soft actuators and robots. Patterning the particles in the hydrogels during fabrication generally requires external magnetic or electric fields, thus limiting the material choice for the particles. Acoustically driven particle manipulation, however, solely depends on the acoustic impedance difference between the particles and the surrounding fluid, making it a more versatile method to spatially control particles. Here, an approach is reported by combining direct acoustic force to align photothermal particles and photolithography to spatially immobilize these alignments within a temperature‐responsive poly(N‐isopropylacrylamide) hydrogel to trigger shape deformation under temperature change and light exposure. The spatial distribution of particles can be tuned by the power and frequency of the acoustic waves. Specifically, changing the spacing between the particle patterns and position alters the bending curvature and direction of this composite hydrogel sheet, respectively. Moreover, the orientation (i.e., relative angle) of the particle alignments with respect to the long axis of laser‐cut hydrogel strips governs the bending behaviors and the subsequent shape deformation by external stimuli. This acousto‐photolithography provides a means of spatiotemporal programming of the internal heterogeneity of composite polymeric systems. Abstract : By exploiting surface acoustic wave and photolithography techniques, photothermal particles are patterned within a thermoresponsive hydrogel matrix to produce composite hydrogel sheets. These sheets undergo programmable swelling and deswelling under temperature change and light exposure, demonstrating applications of autonomous actuators and soft robots.